Clinical and Metabolic Profile of Obese Children at a Tertiary Care Hospital - Sohail Ashraf, Saba Mushtaq, Tahir Mahmood, Sanaa Bibi, Shameen Safdar (Journal of Rawalpindi Medical College, 2021)
ABSTRACT Objective: The aims of our study were to find out the physical features and biochemical complications of obese children presenting to our hospital. Methodology: This Cross-sectional study was conducted in outpatient department (OPD) of POF hospital Wah Cantt from January 2019 to June 2020.Non probability convenient sampling was used to include obese children less than 14 years of age. Child was labeled obese as per W.H.O. criteria. History and complete physical examination was done according to pre designed proforma of all the participants. Blood samples were sent for analysis after taking consent. Results: Total of 100 obese children was included in the study out of whom 62 % were females and 38% were males. Majority were under 10 years of age (70%). Arthralgia (55%) was the most common complaint and Acanthosis Nigricans (31%) was the most common physical finding. Vitamin D deficiency was present in 60% of the cases. Iron deficiency was found more in females (64.5 %) (p value 0.01) and children under 10 years of age (62.8 %) (p value 0.02). Conclusion: Obesity can lead to various health complications. Early detection and prevention of these complications can decrease the associated morbidities and mortalities in adulthood. Key words: Obesity, vitamin D deficiency, Iron deficiency, Anemia, Acanthosis Nigricans